An examination of poverty and sexual orientation in the UK - S. C. Noah Uhrig (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Is there a link between sexuality and poverty? If so, has this relationship changed over time? What anti-poverty policies might be relevant to address issues related to sexuality and poverty? The report synthesises literature and adds top-line findings from the UK Household Longitudinal Study. It finds that gay men, and bisexual men and women experience some degree of material disadvantage as compared to heterosexuals. Lesbian disadvantage may be more related to their status as women than their sexuality. Recommendations concern alleviating sexuality related homelessness, school bullying, health inequalities, earnings disparities and social care needs in old age.
Keywords: I30; Z13; I14; I24; J31; 330; Sexual orientation; Poverty; Homelessness; Aging and retirement; Health inequality; Earning inequality; UK Household Longitudinal Study